Seasonality and the effectiveness of mass vaccination - Dennis L. Chao; Dobromir T. Dimitrov (Mathematical Biosciences and Engineering)
Many infectious diseases have seasonal outbreaks, which may be driven by cyclical environmental conditions (e.g., an annual rainy season) or human behavior (e.g., school calendars or seasonal migration).If a pathogen is only transmissible for a limited period of time each year,then seasonal outbreaks could infect fewer individuals than expected given the pathogen's in-season transmissibility.Influenza, with its short serial interval and long season,probably spreads throughout a population until a substantial fraction of susceptible individuals are infected.Dengue, with a long serial interval and shorter season,may be constrained by its short transmission season rather than the depletion of susceptibles.Using mathematical modeling, we show that mass vaccination is most efficient,in terms of infections prevented per vaccine administered,at high levels of coverage for pathogens that have relatively long epidemicseasons, like influenza, and at low levels of coverage for pathogens with short epidemic seasons, like dengue.Therefore, the length of a pathogen's epidemic season may need to beconsidered when evaluating the costs and benefits of vaccination programs.